Ultrasound-Assisted Lumbar Interlaminar Epidural Dye Injection and Evaluation of Its Distribution by Anatomical Dissection - Evansa, Irina; Krumina, Angelika; Simonova, Anna; Dzabijeva, Viktorija; Fedorovica, Svetlana; Hadunkina, Alla; Zlobina, Natalja; Vabels, Grigorijs; Strike, Eva; Viksna, Ludmila; Vanags, Indulis (Frontiers in Medicine, 2019)
Background. Epidural steroid injections are frequently used to treat lumbar radicular pain. However, the spread of a solute in the epidural space needs further elucidation. We aimed at assessing the distribution of green dye in the epidural space after lumbar epidural injection on cadavers. Methods. We performed ultrasound-guided injections of green dye between lumbar vertebrae 4 and 5 in 24 cadavers. The cadavers were randomly divided into group A and B according to the volume of injected dye; 3 ml in group A (n=13) and 6 ml in group B (n=11). Accuracy of the needle insertion and patterns and distributions of the spread were compared between the groups. After local dissection, we examined the spread of dye in dorsal and ventral epidural spaces and presented the distribution as whole numbers and quartiles of intervertebral segments. Mann-Whitney U Test was used to compare distribution of dye spread between groups A and B. Wilcoxon Signed-Rank Test was used to compare the spread of dye in cranial and caudal direction within the group. We considered P < 0.05 as significant. Results. Data were obtained from all 24 cadavers. Median levels of dorsal cranial dye distribution in groups A and B were 2 and 4 (P=0.02), respectively. In the dorsal caudal - 2 and 2, respectively (P=0.04). In the ventral epidural space cranial dye spread medians were – 0 and 2 in groups, respectively (P=0.04). Ventral caudal spread was 0 and 1, respectively (P=0.03). We found a significant difference between cranial and caudal dye distribution in group B (P<0.05). In group A the dye spread was bilateral. In group B cranial and caudal dye spread was observed. Conclusions. Ventral dye flow was observed in 50% of injections. Bilateral spread of dye occurred in 63%, and more often in group A. Cranial spread was slightly higher than caudal spread in group A despite a smaller injected volume, and significantly higher in group B following a larger volume.